Outcome analysis of the autologous bone grafts for reconstructing acetabular bone defects in total hip arthroplasty for developmental dysplasia of the hip - Zhang, Yong; Lu, Yingjie; Zhang, Yijian; Yang, Huilin; Jiang, Ming; Huang, Lixin (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to retrospectively investigate the short- or medium-term clinical outcomes in patients with Hartofilakidis type II developmental dysplasia of the hip (DDH) after structural bone grafting of the autologous femoral head with a non-cemented prosthesis during total hip arthroplasty (THA).Material and methodsA total of 80 patients (80 hips), including 46 men and 34 women, were enrolled. The age of the patients ranged from 44 to 61 years (mean age: 50.85 ± 9.22 years). The resected femoral head was utilized as a bone graft for the reconstruction of acetabular bone defects above the acetabulum. Preoperative and postoperative leg length discrepancies (LLD) and Harris Hip Score scores were also measured. Lastly, complication occurrence was recorded.ResultsThe LLD decreased from 22.13 ± 11.22 mm before surgery to 4.27 ± 2.15 mm after surgery (P < 0.001). The vertical distance of the hip rotation center reduced from 41.14 ± 12.17 mm before surgery to 20.76 ± 9.91 mm after surgery (P < 0.001). The horizontal distance of the hip rotation center diminished from 40.20 ± 13.33 mm before surgery to 22.61 ± 6.88 mm after surgery (P < 0.001). The HHS score increased significantly from 43.75 ± 12.67 preoperatively to 90.15 ± 8.91 at the final follow-up (P < 0.001). None of the patients experienced fractures during the operation, and there were no postoperative complications such as hematomas or wound infections.ConclusionStructural bone grafting is an effective method for restoring acetabular bone volume and ensuring good acetabular prosthesis coverage in adult patients with DDH who present with intraoperative bone loss during THA.